The Relationship Between Wort Sugar Concentration and Yeast Carbon Partitioning During Brewing Fermentations. (2nd October 2019) - Zhuang, Shiwen; Smart, Katherine; Powell, Chris D.
Abstract: High gravity (HG) and very high gravity (VHG) fermentations are increasingly attractive within the brewing industry as a means of optimizing process efficiency and energy-saving. However, the use of highly concentrated worts is concomitant with a number of biological stress factors that can impact on yeast quality and fermentation performance. In order to eliminate or reduce potentially detrimental effects, brewing yeast respond to their environment by shunting carbon into different metabolic end products, which assist in the protection of cells, but also impact on final ethanol yield. The purpose of this research was to investigate the impact of substrate sugar concentration on carbon partitioning in brewing fermentations. This was conducted using a series of laboratory-scale fermentations with worts of 13°P, 18°P and 24°P, pitched using lager and ale yeast strains. Fermentation performance was assessed with respect to the uptake of wort sugars and the production of key carbon-based metabolites, leading to a calculation of yeast central carbon flux. Analysis of carbon assimilation and dissimilation revealed that changes in intracellular trehalose, glycogen, higher alcohols and esters were observed, however the production of yeast biomass acted as the major trade-off with ethanol production. The data presented here shows for the first time the requirements of yeast populations during HG and VHG conditions and the factors that have a major impact on key performance indicators. This data has major significance for fermentation-based industries globally and is especially important for those sectors seeking to maximize yield from existing resources through high gravity fermentations.